"Social learning in primate communication" - (:unkn) unknown (My University, 2025)
Human language is a highly cooperative and mainly socially learned behaviour, enabled by anatomical and neurological adaptations and a specialised cognitive architecture. Our goal is to describe the evolutionary origins of this cognitive architecture, to understand the major transition that has taken place in human evolution from non-linguistic to linguistic communication. The transition to language was unlikely the result of a single evolutionary event but caused by gradual changes in a number of pivotal components. Some appear to be phylogenetically old, with deep roots in the primate evolutionary history; others may have emerged more recently, after the split between humans and the great apes. Comparative research can help to identify the evolutionary history of these components. In recent years a lot of progress has been made to chart the natural communication and cognition of our closest living relatives, the chimpanzees and bonobos, and of many other species of primates. As a result, there is now good evidence that primates use signals in intentional and referential ways, that they are able to use arbitrary sound patterns to refer to external events, and that signal combinations can be communicatively important for them. One core aspect of language, however – the acquisition of communicative competence -- has received relatively little empirical attention by comparative research. Although there is a large literature on how human infants acquire language, little systematic research has been carried out to understand how non-human primates acquire their communicative capacities and skills. Here, we propose a set of observational and experimental studies to make progress in this domain. Our first approach is to target the full vocal repertoire of different primate species to capture the full acoustic variance and then to look for signs of social learning within the different call types. We will make use of recent advances in computational neurobiology by using algorithms developed in vision research for acoustic feature detection. Our second approach is experimental and will target the question of how sound-meaning linkages are established in primates. To this end, we will carry out a series of experiments with chimpanzees, both in captivity and in the wild, and with several monkey species, particularly Diana monkeys, sooty mangabeys and vervet monkeys in their natural habitats. In doing so, we will pay additional attention to ontogenetic effects by sampling individuals of different age/sex classes. We will use novel infrared thermography to assess social learning in wild animals, in addition to more traditional behavioural measures, such as gaze direction, locomotion and vocal behaviour. Our overall goal is to make progress with an important scientific problem, that is, how primates acquire the ability to socially learn to communicate, by observing and interacting with others, a core component of the human language faculty.
Keywords: Behaviour; Communication; Chimpanzee; Primate; Social; Vocalisation; Cognition